Chronic Supurative Otitis Media in relation to dehiscent of facial canal - Acharya, K; Nepal, MK; Rayamajhi, P; Bhattarai, H; Shrivastuv, RP; Sharma, P (Journal of Institute of Medicine Nepal, 2009)
Background: To observe the pathological findings in CSOM-AA along with, frequency of dehiscence of facial canal and to correlate the type of pathologies found with dehiscence of fallopian canal. Methods: It is the retrospective study conducted in the department of ENT-HNS at Tribhuvan University Teaching Hospital, Nepal of 2 yrs duration April 2004 to April 006. Patients undergoing mastoid surgeries for the CSOM-AA under general anesthesia were taken for the study. Pathological findings were divided into 3 groups which are granulation tissue, cholesteatoma or both. Special attention was given to identify the dehiscent of facial canal and its status was also followed up in postoperative period till 1 month. Results: The pathological finding commonly encountered were cholesteatoma with granulation 75.2% (94), whereas cholesteatoma alone was 18.4% (23) and granulation tissue only was 6.4%(8) The total incidence of facial canal dehiscence was 22 % (28/125) in our study. Horizontal part of the fallopian canal was most common site for dehiscence 50% (14/28) followed by vertical part 35 % (10/28) then both part was involved in 15% (4/28). There is no statistical significance between any type of pathology and dehiscence of facial canal. Conclusion: Cholesteatoma with granulation was the most common pathology found in CSOMAA. Irrespective of the pathologies in the middle ear cleft during mastoid surgeries for CSOM- AA, the facial canal was found to have dehiscence which was commonly occurring at horizontal part of the facial canal with higher incidence among cholesteatoma with granulation group. Keywords: Chronic supurative otitis media, cholesteatoma, granulations, facial canal Journal of Institute of Medicine, August, 2008; 30:2 24-27 The full text of this paper is available from the Journal of Institute of Medicine website